2006
DOI: 10.1016/j.nuclphysa.2006.07.033
|View full text |Cite
|
Sign up to set email alerts
|

All orders breakup of heavy exotic nuclei in a semiclassical model

Abstract: We present a semiclassical and mostly analytical model of elastic neutron breakup reactions for exotic projectiles. Both nuclear and Coulomb induced reactions are considered and the potentials are treated to all orders in the interactions. Furthermore we introduce a technique which allows the use of the full Coulomb potential, thus including all multipoles besides the dipole. Results for deeply bound states as well as for halo initial states are presented and it is shown that experiments on heavy targets would… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…The bound and unbound states of the 11 Be are known to contain significant admixtures of core-excited components [33][34][35], and hence core excitation effects are expected to be important. This has been in fact confirmed in the case of resonant breakup of this nucleus on 1 H [13,14] and 12 C targets [15], using the no-recoil XDWBA method.…”
Section: Application To 11 Be Reactionssupporting
confidence: 56%
“…The bound and unbound states of the 11 Be are known to contain significant admixtures of core-excited components [33][34][35], and hence core excitation effects are expected to be important. This has been in fact confirmed in the case of resonant breakup of this nucleus on 1 H [13,14] and 12 C targets [15], using the no-recoil XDWBA method.…”
Section: Application To 11 Be Reactionssupporting
confidence: 56%
“…Particularly, it is timely to estimate what are the relevant excitations mechanisms for the reaction. In the case of elastic breakup, that we address here, several few-body formalisms have been developed to extract the corresponding cross sections: Continuum-Discretized Coupled-Channels (CDCC) method [2,3], the adiabatic approximation [4,5], the Faddeev/AGS equations [6,7], and a variety of semiclassical approximations [8][9][10][11][12][13]. The CDCC method is based upon an explicit discretization of all channels in the continuum and requires the solution of an extensive set of coupling equations.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in Fig.14, of Ref. [14], we showed that the Coulomb breakup cross section on heavy targets would be negligible compared to the total nuclear breakup cross section for heavy, neutron rich, exotic nuclei in which the valence nucleons are expected to be in d or f orbits and with separation energies of the order of 10 MeV or more. For heavy exotic projectiles such novel type of experiments, namely breakup on a heavy target, would be therefore possible and useful.…”
Section: Coulomb Breakupmentioning
confidence: 76%
“…For light nuclei the weak binding is associated to small angular momentum values of the occupied orbitals and, due to deformation of the nuclear surface, to strong particle vibration couplings which are at the origin of shell inversion effects [1]. Thus in the extreme case of halo nuclei such as several beryllium and lithium isotopes ( 11 Be, 12 Be, 14 Be, 11 Li), S n is even less than 1 MeV and the valence orbitals are s or p. As a consequence as much as 10% to 40% of the total reaction cross section is due to just one or two channels: 1n or 2n breakup and/or transfer to target bound states depending on the most favorable matching conditions. Therefore, out of necessity (N. Orr), breakup has been one of the most studied reactions for low intensity beams and the one for which several new models have been developed.…”
Section: Introductionmentioning
confidence: 99%